FOLIO: The Future of Library is Open - Chauhan, Satbir; Kandhasamy, K.; Sakthivel, N. (Journal of Information and Knowledge, 2023)
Ranganathan's 5th law of library science says that libraries never become stagnant. While financial constraints are a common challenge for libraries, user expectations are continuously growing. To meet and exceed user expectations, libraries must embrace new technologies and software solutions. Open-source options have proven to be particularly beneficial for nonprofit organizations like libraries. Looking to the future, as libraries continue their digital transformation, many library automation software, especially traditional library management systems (ILS), are becoming outdated. In response to the diverse requirements of libraries, the architecture of Library Services Platforms (LSP) offers enhanced flexibility and functionality within a unified platform. Among the various LSPs that have emerged over the past seven years, FOLIO has demonstrated rapid development and progress. Upon exploration, it becomes evident that FOLIO's developers have prioritized a micro-services architecture, emphasizing apps over modules. This approach provides a comprehensive multitasking app environment, a user-friendly Dashboard for quick access, efficient data management, and much more. The user-friendly nature of FOLIO sets it apart from traditional Integrated Library Systems (ILS), which may lack such ease of use. Despite its abundant features, FOLIO is still relatively under-recognized in India. This paper aims to discuss the distinctive features of FOLIO, it’s potential as a comprehensive solution for libraries, and whether it can effectively replace traditional ILS systems.